PENGARUH KUALITAS PELAYANAN PT. PLN (PERSERO) TERHADAP KEPUASAN PELANGGAN DI KOTA AMBON (STUDI KASUS PELANGGAN RUMAH TANGGA TARIF 900 VA). - Eline Octoviana Hutubessy; Simson Melmambessy; Victorio Fernando Nahuway (Jurnal Administrasi Terapan, 2023)
This study aims to determine: (1) The service quality of PT. PLN (Persero) in Ambon City. (2) The level of customer satisfaction of PT. PLN (Persero) in Ambon City. (3) Influence of PT service quality. PLN (Persero) on customer satisfaction in Ambon City. This type of research is quantitative. Data collection techniques were carried out through literature and field research in the form of observations, questionnaires, agency data and documentation. The total population for the study was 24,332 with a random sample of 100 people. The analytical method used is the Simple Linear Regression method.The results showed that the indicators of Service Quality at PT. PLN (Persero) in Ambon City is good because the percentage of Service Quality has high values or a high percentage, especially on the Empathy indicator. Customer Satisfaction at PT. PLN (Persero) in Ambon City is very good because Customer Satisfaction is higher than Service Quality, which means that customers in Ambon City are very satisfied with the service or performance of the service provider (PT. PLN). Service Quality has an effect on Customer Satisfaction, from the regression model, significant results are obtained and the percentage value is 66 percent.Keywords: Service quality